The birth of forceps. Issue 7 (5th June 2013) - Sheikh, Sukhera; Ganesaratnam, Inithan; Jan, Haider
Operative vaginal delivery has been described since the Middle Ages. During this time, however, labour would be sustained over several days and intrapartum death almost inevitable. In these circumstances, intervention involving the use of surgical instruments or even kitchen utensils would serve purely as an attempt to avoid maternal mortality. The establishment of forceps-assisted delivery as a means of avoiding both maternal and neonatal morbidity was initiated in the 16th century by the Chamberlen family and later developed over several centuries by leading obstetricians of the time including Simpson, Barnes and Keilland. The evolution of forceps is a fascinating story which is rich in history. Despite the development of Ventouse and the increasing use of Caesarean section for difficult delivery, forceps remain an integral part of obstetric practice. The striking resemblance of modern day forceps to the original instruments used by the Chamberlens is a testament to both the family's ingenuity and enterprise as well as the subsequent pioneering obstetricians who followed in their footsteps.